Volume 3 2004
DOI: 10.1115/ht-fed2004-56419
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Flow in a Large Quench Tank

Abstract: A computational fluid dynamics (CFD) model is developed to simulate isothermal flow in a large quench tank used for heat treating of steel. As a surrogate for a full simulation of quenching, the isothermal model enables a computational economical comparison of many different design configurations of the quench tank. The model includes most of the geometric complexity of the tank including the skip, the heavy beams used to support it, deflector baffles used to control the flow, and the inlet ducting. Partial fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Recently CFD analysis was conducted with the objective of obtaining an understanding of the flow in an existing quench tank and to use these results to provide innovative design concepts for a new quench system design. The performance of the various designs evaluated was determined using Taguchi partial factorial statistical analysis methodology and this data was used to simulate fluid flow in the design of a commercial quench tank 25 .…”
Section: Use Of Computational Fluid Dynamics (Cfd) In Quench System Dmentioning
confidence: 99%
“…Recently CFD analysis was conducted with the objective of obtaining an understanding of the flow in an existing quench tank and to use these results to provide innovative design concepts for a new quench system design. The performance of the various designs evaluated was determined using Taguchi partial factorial statistical analysis methodology and this data was used to simulate fluid flow in the design of a commercial quench tank 25 .…”
Section: Use Of Computational Fluid Dynamics (Cfd) In Quench System Dmentioning
confidence: 99%
“…Nailu Chen et al [5] investigated the effect of flow directors in quenching with agitation produced by a propeller to evaluate the uniformity of the velocity and distribution of the flow in the quenching area of the piece and thus obtain a more homogeneous cooling of the pieces. On the other hand, experiments have been carried out under steady-state conditions [6,7]. Halva and Volný [8] calculated the fluid flow to examine the homogeneity of the distribution of velocities as a function of the location of the stirrers.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows that from the early 1990s to the beginning of this 21st century, computational fluid dynamics (CFD) focused on isothermal fluid flow calculations. In these works [4][5][6][7][8][9], the Navier-Stokes and continuity equations were numerically solved together with turbulence equations under steady state conditions. The pioneering work of Totten et al [4] showed that flow is not uniform in quenching tanks.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the location of spray eductors around a rack of aluminum panels on flow homogeneity was studied by Bogh [7]. Isothermal fluid flow simulations were computed by Kernanzhitskiy [8], who used these results combined with Taguchi partial factorial statistical analysis methodology to provide innovative design concepts for a new quenching system design. Kumar et al [9] evaluated flow uniformity around automotive pinion gears during quenching.…”
Section: Introductionmentioning
confidence: 99%